Optimization Strategies for Recruitment to Improve Human Resource Quality at Artha Jaya Motor Workshop - Dini, Yuli Indah Fajar; Zhang, Ricky (Pakis Journal Institute, 2025)
Artha Jaya Motor Workshop in Sagulung, Batam, faces challenges in workforce recruitment and human resource management. Traditional recruitment processes are considered inefficient, while the lack of a clear organizational structure impacts the workshop’s operations. To address these issues, a practical work project was carried out focusing on modern recruitment strategies using social media and digital platforms such as Google Form. The goal of this project is to improve recruitment effectiveness, establish an efficient organizational structure, and reduce employee turnover by creating clear work contracts. The outcomes of this activity are expected to support the growth of Artha Jaya Motor Workshop and positively contribute to the local economy.